Use of aggregates from construction waste in asphalt paving base - Vertuan, João Vitor Costa; Gregui, Ana Paula Moreno Trigo (Seven Editora, 2023)
Nowadays, with the growing increase in the urban demographic aspect, it is a social priority to propose measures to mitigate the problems encountered and to subsidize actions, in order to correct and avoid future complications in areas conducive to urban expansion. DOI:https://doi.org/10.56238/interdiinovationscrese-090